The Epstein-Glaser causal approach to the light-front QED(4). II: Vacuum polarization tensor - Bufalo, R. [UNESP]; Pimentel, B. M. [UNESP]; Soto, D. E. [UNESP] (Elsevier B.V., 2014)
In this work we show how to construct the one-loop vacuum polarization for light-front QED(4) in the framework of the perturbative causal theory. Usually, in the canonical approach, it is considered for the fermionic propagator the so-called instantaneous term, but it is known in the literature that this term is controversial because it can be omitted by computational reasons; for instance, by compensation or vanishing by dimensional regularization. In this work we propose a solution to this paradox. First, in the Epstein-Glaser causal theory, it is shown that the fermionic propagator does not have instantaneous term, and with this propagator we calculate the one-loop vacuum polarization, from this calculation it follows the same result as those obtained by the standard approach, but without reclaiming any extra assumptions. Moreover, since the perturbative causal theory is defined in the distributional framework, we can also show the reason behind our obtaining the same result whether we consider or not the instantaneous fermionic propagator term. (C) 2014 Elsevier Inc. All rights reserved.
Keywords: Light-front field theories; Epstein-Glaser causal method; Radiative correction